Transforming Health Care Through Interprofessional Graduate Education. Issue 1 (27th September 2016) - Beebe, Lora Humphrey; Roman, Marian; Raynor, Hollie; Thompson, Dixie; Ray, Shaunta
Abstract : PURPOSE: We provide an overview of the Recovery‐based Interprofessional Distance Education (RIDE) rotation for graduate students in psychiatric mental health (PMH) nursing, pharmacy, nutrition, and exercise physiology, with faculty from the four professions represented. CONCLUSIONS: Interprofessional education can enhance team concepts in these professions and is viewed positively by students and faculty. PRACTICE IMPLICATIONS: Interprofessional learning opportunities prepare graduates to contribute to team‐based care. We urge colleagues to join us in providing meaningful IPE experiences to students at all levels, with the goal of optimizing health care for all persons with mental health treatment needs.